GEOTECHNICAL CHARACTERISTICS OF THE BANKS IN THE MIDDLE COURSE OF THE NERETVA RIVER THROUGH THE CITY OF THE MOSTAR - Goran Šunjić; Tatjana Džeba; Maja Prskalo (e-Zbornik. Elektronički Zbornik Radova Građevinskog Fakulteta, 2020)
Regulation Plan for the historic town area of Mostar includes major aspects of preservation and development of historic town zones. Provisions of the Regulation Plan pertain to use of land and buildings, aiming to preserve and revive the traditional uses and protect the natural characteristics of the area [8]. In this respect, the historic area of the town of Mostar has been divided into ten zones according to the use of land and structures, and Zone 8 covers Neretva as a protected riverside zone. The study aimed to define causes and state of weathering, damage and stability of rocks, then to define the existing state in terms of geological structure, and visit the most critical sections that require improvement.